Superalloys 2012 (Twelfth International Symposium) 2012
DOI: 10.7449/2012/superalloys_2012_863_872
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and the Effects of High Temperature Exposures on Notched Fatigue Life of an Advanced Powder Metallurgy Disk Superalloy

Abstract: Oxidation and the effects of high temperature exposures on notched fatigue life were considered for a powder metallurgy processed supersolvus heat-treated ME3 disk superalloy. The isothermal static oxidation response at 704 °C, 760 °C, and 815 °C was consistent with other chromia forming nickel-based superalloys: a TiO 2 -Cr 2 O 3 external oxide formed with a branched Al 2 O 3 internal subscale that extended into a recrystallized γ'-dissolution layer. These surface changes can potentially impact disk durabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Compared with the studies of isothermal oxidation/cyclic oxidation for the disc alloys, the oxidation under (cyclic) stress exhibits a greater discrepancy between grain boundary and grain interior [12,22]. The grain boundary oxidation is much more significant than that in the grain interior.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Compared with the studies of isothermal oxidation/cyclic oxidation for the disc alloys, the oxidation under (cyclic) stress exhibits a greater discrepancy between grain boundary and grain interior [12,22]. The grain boundary oxidation is much more significant than that in the grain interior.…”
Section: Discussionmentioning
confidence: 92%
“…indicates that the GBs without bulged Co-rich oxide complex are decorated with a Ni/Ti/Alrich oxide complex. Additionally, it is found that the content of Al is lower than its original content either at GBs or within grains and the content of Cr is relatively higher than its original content within grains, this is believed to be associated with the formation of an internal alumina layer and an outer layer of chromium oxide as observed in Ni-based superalloys [12,18,22,[27][28][29]. However, it should be noted that point out that the elements in the regions nearby and underneath the GB oxides may also contribute to the composition of the GB oxides due to the relatively large electron beam size used for EDS analysis and the large activation volume.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These alloys were consolidated from powder atomized in argon, then extruded and isothermally forged into disks. Blanks were extracted from the rim of fully heat treated ME3 disks [14] and the bore of a fully heat treated Udimet 720 disk [15], which each had been previously studied. Rectangular blanks of LSHR were extracted and separately heat treated.…”
Section: Materials and Proceduresmentioning
confidence: 99%